2017
DOI: 10.1155/2017/7940851
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Meckel’s Diverticulum in Children: The Diagnostic Value of Double-Balloon Enteroscopy

Abstract: Background. Meckel's diverticulum (MD) is the most common congenital anomaly of the gastrointestinal tract. The purpose of this study was to evaluate the diagnostic value and safety of double-balloon enteroscopy (DBE) for bleeding MD in children. Methods. We included consecutive children who were highly suspected of MD between 2012 and 2013. All patients underwent Meckel's scan. DBE was performed for patient with negative Meckel's scan. An exploratory laparoscopy was performed in children with positive Meckel'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The distances between MD site to ileocecal valve measured by DBE was 60 to 100 cm (mean ± SD=81.0 ± 16.0 cm), while surgery found that the distances were 30 to 100 cm (mean ± SD =71.0 ± 18.5). These findings are consistent to that reported by Geng et al [ 20 ] There is no statistical difference between DBE and surgical measurements. Therefore DBE can accurately locate the MD bleeding sites and reliably provide guidance for surgical treatment of MD bleeding.…”
Section: Discussionsupporting
confidence: 93%
“…The distances between MD site to ileocecal valve measured by DBE was 60 to 100 cm (mean ± SD=81.0 ± 16.0 cm), while surgery found that the distances were 30 to 100 cm (mean ± SD =71.0 ± 18.5). These findings are consistent to that reported by Geng et al [ 20 ] There is no statistical difference between DBE and surgical measurements. Therefore DBE can accurately locate the MD bleeding sites and reliably provide guidance for surgical treatment of MD bleeding.…”
Section: Discussionsupporting
confidence: 93%
“…Gastrointestinal bleeding presenting with bloody stool related to an MD is caused by ulceration of the small bowel due to acid secretion by ectopic mucosa within the diverticulum or rarely from adjacent ileal ulcers secondary to acid secreted in an MD. Bleeding is reported clinically as acute massive hemorrhage, anemia due to chronic bleeding, or self-limiting recurrent episodes (17). Transfusions are uncommonly reported for Meckel's-associated bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies involving large populations have demonstrated that double balloon enteroscopy has higher diagnostic accuracy than scintigraphy. In addition, it allows treatment in some cases although it is limited (Geng et al, 2017). However, its disadvantages are that it is technically difficult, it is not available in most endoscopy centers, and optimal imaging cannot be obtained due to blood and bleeding residues accumulated in the lumen during bleeding.…”
Section: Discussionmentioning
confidence: 99%